1990
DOI: 10.1002/ar.1092260408
|View full text |Cite
|
Sign up to set email alerts
|

Melano‐macrophage centers in the aglomerular kidney of the sea horse (Teleosts): Morphologic studies on its formation and possible function

Abstract: In order to elucidate the process of the formation and possible function of the renal "melano-macrophage centers (MMC)" of fish, light and electron microscopic observations were carried out on the aglomerular kidney of the sea horse, Hippocampus kuda BLEEKER, injected with antigenic horse-spleen ferritin (AF) and nonantigenic carbon particles (CP). Kidneys of the sea horse have well-developed hemopoietic foci in the interstitial tissues surrounding the bundles of renal tubules. Each hemopoietic focus has a sma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0
4

Year Published

1996
1996
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 33 publications
1
35
0
4
Order By: Relevance
“…In the last decade, several studies have exposed links between pollution and health of fishes and other marine organisms (Roberts, 1985;Fournie et al, 2001;Cajaraville et al, 2003). In fishes, according to various authors (Tsuji and Seno, 1990;Fredello et al, 2001), larger aggregations of macrophages or melano-macrophage centers, normally found in the lymphatic and other organs, are involved in various processes of phagocytosis, storage, and detoxification of bacteria and alien materials. Micale and Perdichizzi (1990) demonstrated that increased numbers of melano-macrophage centers in the fish spleen are induced by environmental factors and not only by tissue catabolism.…”
Section: Discussionmentioning
confidence: 97%
“…In the last decade, several studies have exposed links between pollution and health of fishes and other marine organisms (Roberts, 1985;Fournie et al, 2001;Cajaraville et al, 2003). In fishes, according to various authors (Tsuji and Seno, 1990;Fredello et al, 2001), larger aggregations of macrophages or melano-macrophage centers, normally found in the lymphatic and other organs, are involved in various processes of phagocytosis, storage, and detoxification of bacteria and alien materials. Micale and Perdichizzi (1990) demonstrated that increased numbers of melano-macrophage centers in the fish spleen are induced by environmental factors and not only by tissue catabolism.…”
Section: Discussionmentioning
confidence: 97%
“…Earlier studies have demonstrated that injected particulate material (Salmonella bacteria) and soluble particles (carbon) accumulate in melanomacrophages (Roberts 1975, Ellis et al 1976, Ferguson 1984, Tatner & Manning 1985. In addition, it has been suggested that melanomacrophages are composed of accun~ulations of sinusoidal macrophages, that have ingested foreign material and (perhaps) moved into the interstitial tissues (Vogelbein et al 1987, Tsjuii & Seno 1990, Brattgjerd & Evensen 1996. The positive imrnunostaining of sinusoidal macrophages most likely reflects the ability of this cell population to phagocytize particulate material, as also observed for latex particles ( S m e d s r~d et al 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Fish species are also known to alter their appearance when ill or under stressful and hazardous conditions, by visibly appearing either paler or darker in color (Wallbrunn, 1957). Melanophores in some teleost species even associate with macrophages in hematopoietic tissue to form melanomacrophage centers, and may play a role in host immune defenses (Agius, 1980;Ellis and Munroe, 1976;Roberts, 1975;Tsujii and Seno, 1990). The many physiological functions that chromatophores possess impart the versatility of using these cell types in vitro to sense varying agents.…”
Section: Discussionmentioning
confidence: 97%